Inflammation induced by inhaled lipopolysaccharide depends on particle size in healthy volunteers. (28th July 2016) - Doyen, Virginie; Pilcer, Gabrielle; Dinh, Phong Huy Duc; Corazza, Francis; Bernard, Alfred; Bergmann, Pierre; Lefevre, Nicolas; Amighi, Karim; Michel, Olivier
Abstract : Aims: In drug development, the anti‐inflammatory properties of new molecules in the lung are currently tested using the inhaled lipopolysaccharide (LPS) model. The total and regional lung bioavailability of inhaled particles depends significantly on their size. The objective of the present study was to compare inflammatory responses in healthy volunteers after the inhalation of LPS of varying droplet size. Methods: Three nebulizers were characterized by different droplet size distributions [mean mass median aerodynamic diameters: Microcirrus (2.0 μm), MB2 (3.2 μm) and Pari (7.9 μm)]. Participants inhaled three boluses of a 20 μg (technetium 99 m‐labelled) solution of LPS, randomly delivered by each nebulizer. We measured the lung deposition of the nebulized LPS by gamma‐scintigraphy, while blood and sputum biomarkers were evaluated before and after challenges. Results: MB2 and Pari achieved greater lung deposition than Microcirrus [171.5 (±72.9) and 217.6 (±97.8) counts pixel –1, respectively, vs. 67.9 (±20.6) counts pixel –1 ; P < 0.01]. MB2 and Pari caused higher levels of blood C‐reactive protein and more total cells and neutrophils in sputum compared with Microcirrus ( P < 0.05). C‐reactive protein levels correlated positively with lung deposition ( P < 0.01). Conclusions: Inhalation of large droplets of LPS gave rise to greater lung deposition and induced a more pronounced systemic and bronchial inflammatory response than small droplets. The systemic inflammatory response correlated with lung deposition. NCT01081392.